Compliance With Epidemic Prevention Guidelines Among Wuhan Citizens Under the Stressors of the COVID-19 Pandemic: A Cross-Sectional Multidistrict Comparative Analysis - Wang, Xuelian; Cai, Yuwei (Frontiers in Psychology, 2022)
The current study aims to compare compliance with the COVID-19 prevention guidelines among citizens from 13 districts in Wuhan and to explore the influence of individual-level psychological factors and district-level factors on compliance. A total of 811 participants (52% females) from 13 districts in Wuhan were invited to complete surveys regarding demographics, psychosocial factors and compliance with epidemic prevention guidelines. Individual-level characteristics were combined with district-level measures to create multilevel predictive models of compliance with prevention guidelines, and used the Hierarchical Linear Model (HLM) to analyze the data. Findings revealed that there were significant differences in the compliance of citizens from 13 districts of Wuhan (F=5.65, P < 0.001). Hierarchical linear model analysis revealed that the risk factors case growth rate, COVID-19-related perceived stress, anxiety, significantly negatively predicted compliance. Hope and conscientiousness significantly positively predicted compliance with prevention guidelines, and the negative predictive effect of anxiety disappeared. Overall, we found significant differences in compliance with prevention guidelines among different districts. Risk factors at the individual level have had a negative impact on individuals' compliance with prevention guidelines, but this impact can be mitigated by the positive role of personal protective factors such as conscientiousness and hope.